Satellite image 1:500 000 Borgmassivet, Penckmulde, Neumayersteilwand, Antarktis ... - Brunk, Karsten (Institut für Angewandte Geodäsie (Now: Bundesamt für Kartographie und Geodäsie) Frankfurt am Main, 1986)
Landsat-1 imagery, supplemented with geographical names, 182/112, 27 January 1974; Annex 9 of 17, Brunk, K. (1986);Scale: 1:500000;Bounding Box: POLYGON ((-3 -71.95, 1.75 -72.84, -1.09 -74.23, -6 -73.25, -3 -71.95)) ...